PERALIHAN MATA PENCAHARIAN MASYARAKAT PETANI DI KAMPUNG VASCODAMNEEM DISTRIK MEYADO KABUPATEN TELUK BINTUNI - Abdul Maulana Yusuf; Kunto Wibowo; Ardha Puspita Sari (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2023)
The people of Vascodamneem Village are a transmigration community in 1997, the majority of whom make their living as farmers. Agriculture in Vascodamneem Village survived until 2012 and the farming community began to shift their livelihoods to oil palm plantation labor. Therefore, research is needed to determine the factors causing the shift in livelihoods and the impact on agricultural land. This research aims to (1) determine the factors causing the shift in livelihoods from rice farmers to oil palm plantation workers (Elaeis guineensis jacq); (2) knowing the impact of changing the livelihoods of rice farmers to oil palm workers (Elaeis guineensis jacq). The method used in this research is a descriptive method with case study techniques. This research data collection includes (1) primary data and (2) secondary data. Primary data was collected using the interview method using a questionnaire. Secondary data was obtained from various types of literature and various related agencies. The research results show that the driving factors that influence are income as a farmer with an average score of 5, risks in farming with an average score of 4.4, agricultural facilities with an average score of 4.75. The influencing pull factors are wages and income with an average score of 4.5, working conditions with an average score of 3.27, employment facilities with an average score of 4. The impact on land from the transition of livelihoods, namely agricultural land to idle land (uncultivated land).